Analysis of Requirements for Inhalation Toxicity Studies of Chemicals - A. O. Verner; T. M. Ustinova; Yu. O. Kon’shakov; N. G. Vengerovich (Регуляторные исследования и экспертиза лекарственных средств)
SCIENTIFIC RELEVANCE. Studies of the inhalation administration of chemicals are associated with challenges in designing experiments. The parameters to be selected include the experimental animal species, the inhalation chamber, and the mode of inhalation (dynamic or static).AIM. This study aimed to analyse the practical application of regulatory requirements to non-clinical studies of the inhalation toxicity of chemicals.DISCUSSION. This review compares international and Russian standards for studying the inhalation toxicity of chemicals, including GOST 32542-2013, GOST 326432020, GOST 32636-2020, GOST 32383-2013, and GOST 2646-2014. The improvement of the legal and regulatory framework correlates with adopting the Good Laboratory Practice and the risk-based approach to categorising test substances into hazard classes. Hazard classes are determined in rodents without dose extrapolation to humans. The authors present the differences between the main guidelines on inhalation exposure in rodent studies of acute, subacute, subchronic, and chronic toxicity. The article describes current approaches to assessing the inhalation toxicity of chemicals, which allow researchers to replace animal studies with in vitro tests.CONCLUSIONS. According to the current regulatory standards, inhalation toxicity is studied in rats/mice, which have anatomical differences from humans. As an alternative to animal studies, researchers are developing and validating in vitro methods, which yet require regulatory review and approval.